The structure elucidation of new mono-core dicationic salt-containing chlorosulfonate counterion: Raman study of a pure sample of chlorosulfonate anion in the solid and liquid state - Zaharani, Lia; Khaligh, Nader Ghaffari; Shahnavaz, Zohreh; Johan, Mohd Rafie (Elsevier, 2020)
This paper presents the design and synthesis of new ionic liquid containing dication of 1H,4H-piperazine-diium ring and two chlorosulfonate as counterions. The structure elucidation of new ionic organo-compound was performed by 1D and 2D NMR, FTIR, Raman, and mass spectrum. Then, the correct structure was elucidated by COSY which was supported by Raman study. IR and Raman spectra of liquid and solid-state of 1H,4H-piperazine-diium dichlorosulfonate are studied. Assignments are made for FTIR and Raman peaks, and our results are compared with previous reports in the literature. © 2020 Elsevier B.V.